CT Scan Imaging of the Human Fetal Labyrinth: Case Series Data Throughout Gestation. Issue 5 (June 2016) - Mejdoubi, Mehdi; Dedouit, Fabrice; Mokrane, Fatima-Zohra; Telmon, Norbert
Abstract : Objectives: The inner ear in humans reaches its final configuration and its adult size during fetal life. According to the literature, this occurs between 18 and 25 weeks of amenorrhea (WA). Our goal is to clarify the course of inner ear size development. Methods: Using computed tomography (CT) scanner, we studied 13 measurements in the inner ear of a collection of 153 fetuses from 21 to 40 WA. Results: We found no side-related differences or sexual dimorphism in the measurements. Cochlear and vestibular bone measurements did not show growth from 21 to 40 WA, with the exception of the lateral semicircular canal (LSCC) bony island, which grows until 25 WA. Internal auditory canal (IAC) and cochlear aqueduct (CA) growth are correlated with gestational age. As our cochlear measurements are similar to those of infants and adults, in accordance with the literature we conclude that the cochlea has reached its adult size before 21 WA. The continuous growth of the IAC and CA is linked to petrous ossification that continues during fetal gestation and after birth. Conclusion: We confirm that the cochlea reaches its adult size during the second trimester of fetal life.